PERSEPSI MASYARAKAT TERHADAP SANKSI DAN MANFAAT PERKAWINAN SESUKU DI DESA LUBUK BENDAHARA KABUPATEN ROKAN HULU - Nurhakiki, Nurhakiki; Hambali, Hambali; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: this research is motivated by the function and benefits of tribal marriage in the determination of tribal marriages sanctions for tribal mariagges and the benefits of tribal marriage for the people of Lubuk Bendahara in theirdaily lives. The formulation of the problem of this research is “how is the community’s perception of the tribe sanctions and how is the community’s perception of the benefits of the tribal marriage in the Lubuk Bendahara Timur village, Rokan Hulu district”. The purpose of this study was to providein the vilage of Lubuk Bendahara in Rokan Hulu district and practically the results of this research were expected to increase knowleadge for thereaders and the readers and add the researcher’s own knowledge. Data collection techniques in this study were observation, interviews and documentation. The study respondents took a sampleof 5 people, 2of whom conducted inter-etnic marriage from community informants representing the community in the village of Lubuk Bendahara Timur. Data analysis techniques in this study used qualitative methods. The resultsof this study were the public perception of witnesses being fitnedwith a cow/buffalo orin the form or a four-legged animal, the perpetrators were finrd from another tribe and if the fines were not the Lubuk Bendahara village. The benefits of inter-ethnic marriage in the village of Lubuk Bendahara in Rokan Hulu district, the nephew has a positive sense of value, the nephew will get relatives, and the nephew feels the bondage has a good value in the eyes of mamak ninik and the community and nephew have followed the customs. Well, in the family or in religious law where witnesses of tribal marriage are given to perpetrators based on are considered normal and are common in the community.Key Words: Perception,Tribal Marriage